The toppling of caricism and the revival of ukrainian statehood in the historical and legal literature of the diaspora scientists in 20–30 yrs. of the XXth century - Tokarchuk, O. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract The formation of Ukraine as an independent state is in the sphere of state policy towards the Ukrainian diaspora, including in the context of Ukraine's cooperation with foreign Ukrainians. The study of the problems of the revival of Ukrainian statehood in the works of the Diaspora scientist in 20-30 yrs. of the 20th century is great importance for the development of historical and legal science, because the coverage of the participation of Ukrainian intellectuals in emigration in the process of establishing a democratic and legal Ukraine, first of all, lobbying national interests of our state in the international arena and in different countries of the world, remains insufficiently researched. Thus, in the modern period, the attention of scientists to the creative development of Ukrainians in emigration has considerably increased; this has become one of the aspects of interest in the activities of Diaspora lawyers. The goal of the research is to complement the process of thoroughly rethinking the concepts and interpretations of the problem as a whole, as well as its individual elements in particular. The fruitful scientific activities of the Ukrainians in Prague, such as S. Dnistryanskyi, S. Shelukhin and A. Yakovliv, requires the application of new methodological approaches according to which the activities of diaspora scientists should be regarded as a natural consequence of those state-legal realities in which they were. As for the study and evaluation of the Ukrainian state-building of the said legal scientists, it is appropriate to refer to the national-democratic direction. The research and analysis of the works of scientists-emigrants, which reflects the legal justification of the grounds of Ukrainian statehood, the desire of the Ukrainian diaspora for the restoration of national statehood, should cause a considerable interest both by professional scientists and representatives of state authorities, domestic and foreign Ukrainian public-political organizations, the world community and it can be of public benefit under the current difficult conditions of the Ukrainian state-building.